The 50-year history of anglers' record catches of genus Carassius: circumstantial evidence of wiping out the native species by invasive conspecific - Marek Šmejkal; Kiran Thomas; Vladimír Kořen; Jan Kubečka (NeoBiota, 2024)
Successful invasive non-native fish species can cause enormous damage to native biodiversity. In mainland Europe, the introduction of the gibel carp (Carassius gibelio) has led to a decline in populations of the formerly widespread native crucian carp (C. carassius). Both invasive and native species develop two phenotypes, namely stunted and deep-bodied, which depend on the intensity of competition and predation in the water body. The deep-bodied phenotype is associated with a more diverse fish community composition, can attain large sizes and is very attractive to recreational anglers. This study analysed trends in the record sizes of native crucian carp and invasive gibel carp (individuals close to the maximum attainable size of the species) reported by recreational anglers over the last 50 years in Czechia, recording the invasion of gibel carp from its beginnings to the fully established population phase. The study provides circumstantial evidence that gibel carp is behind transition from the relative abundance of large crucian carp to near extirpation, while large gibel carp have taken over the reports of record catches in the genus Carassius. This indicates that the crucian carp, which is currently classified as critically endangered in the Red List of Czechia, has very limited possibilities to realise its deep-bodied phenotype. It also shows the potential of using data from recreational anglers for mapping invasion processes and as a source of relatively localised information on endangered species.